Pachyonychia congenita type 1 with cutaneous pseudohorns. - Kansal, N.K.; Agarwal, S.; Joshi, U.; Choudhary, B.C.; Pant, P. (European Journal of Pediatric Dermatology, 2015)
Pachyonychia congenita is an inherited disorder of keratinization. Its prominent diagnostic feature include wedge-shaped nail dystrophy along with palmoplantar keratoderma. Based on current clinico-genetic data, pachyonychia congenita is classified in five distinct types. We hereby describe a case of pachyonychia congenita type 1 with cutaneous pseudohorns.